Cultural Context In Translation Studies: The Arabic Translation Of Chin P'ing Mei As An Example - Qi Cheng (Ijaz Arabi Journal of Arabic Learning, 2026)
Contextual culture represents one of the core challenges in cross-linguistic translation, particularly when a work carries a dense concentration of cultural information. Framed within Edward Hall’s theory of high-context and low-context culture, this study examines how contextual culture is handled in the complete Arabic translation of Chin P’ing Mei. The research draws exclusively on the bilingual edition translated and annotated by Zhang Hongyi and included in the Library of Chinese Classics. Employing a combination of qualitative case study and textual comparison, the study selects representative passages from three dimensions—material culture, poetic culture, and dialectal culture—and conducts a comparative analysis between the source and target texts to identify the types of strategies employed by the translator in addressing the profound cultural differences between the Chinese and Arabic linguistic systems, as well as the effectiveness of these strategies. Through a comparative analysis between Chinese and Arabic, the study reveals that the translator’s approach is characterized by systematic cultural mediation: amplification is used to supply background information absent in the Arabic context; reduction serves to avoid redundancy or comprehension difficulties arising from cultural differences; explanatory translation resolves the untranslatability of certain images and metaphors in the target language; and syntactic transformation aligns the translation with the grammatical structures and stylistic conventions of Arabic.